Awareness and management of endocrinologists from the Philippines on the interrelationship between diabetes and periodontal disease - Quintos, Francheska Martina R.; Quintos, Francheska Martina R.; Zara, Patricia Mae M.; Estrera, Kristina Rachelle P. (Faculty Co-Author).; Murjani, Bhabita V. (Faculty Co-Author).
Objective: To determine the awareness on the interrelationship between diabetes and periodontal disease among endocrinologists from the Philippines.
Methods: A 20-item self-administered survey questionnaire was distributed to endocrinologists from the Philippine Society of Endocrinology, Diabetes and Metabolism during the Philippine Society of Endocrinology, Diabetes, and Metobolism (PSEDM)-Eli Lilly Diabetes Updates, General Assembly & Endocrination held last September 5-6, 2015 at Sofitel Manila, CCP Complex Roxas Boulevard, Pasay City, Manila. The questionnaire comprised of 8 multiple choice and 12 yes or no questions. Questions included were about demographics of the patient, associations between diabetes and periodontitis, and patient management.
Results: Majority of the endocrinologists answered that both brushing and flossing should be performed at least twice a day (48.9%) and dental visits should be at least once every 6 months (71.3%) to maintain oral health. Most claim to be aware of the manifestations of gingivitis and periodontitis. However, results showed that only a few, 3.6% and 3% respectively, were able to accurately identify the symptoms of the two diseases. Majority knew that poor oral health or PD can affect DM (79.2%) and the DM can also be a risk factor to periodontitis (95.9%). However, only 38.6% considered infection as a risk factor to DM. More than half of the respondents refer their patients to dentists however, less that half actually performs oral health education.
Conclusion: Majority of the endocrinologists is aware of the bi-directional relationship of periodontal disease and diabetes mellitus, but do not clearly know the difference between gingivitis and periodontitis. Their awareness is not observed and translated into how they manage the diabetic patients.
Keywords: awareness, diabetes, endocrinologists, management, periodontal disease.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Endocrinologists; Periodontal disease; Diabetes; Awareness; Management